Friday

September 4, 2015
Posted by **Julie** on Thursday, April 12, 2012 at 12:27am.

a) y = (x² + x - 1)Sin²x

b) y = (x² + 1)/Sin²x

- Calculus grade 12 -
**Steve**, Thursday, April 12, 2012 at 10:50amchain rule:

d/dx sin^2 x = 2(sinx)(cosx) = sin2x

a)

y = (x^2+x-1)sin^2 x

y' = (2x+1)sin^2 x + (x^2+x-1)sin2x

b)

y = (x^2+1)/sin^2 x

y = (2x*sin^2 x - (x^2+1)*2*sinx*cosx]/sin^4 x

= [2x*sinx - (x^2+1)*cosx]/sin^3 x

- Calculus grade 12 -
**Julie**, Thursday, April 12, 2012 at 11:53amThank you Steve